P 84 Progressive ataxia as leading symptom of chronic neuroborreliosis. Issue 10 (October 2017) - Dellen, C.; Pesendorfer, L.M.; Isenmann, S.
Abstract : Case report: A 58-year-old female presented with a slowly progressive ataxic gait disorder for about 6 months. She also reports a recent bladder emptying disorder. Moreover, her husband had observed short-term memory loss with his wife. Her past medical history was uneventful. In clinical examination, an atactic finger-nose test and knee-jaw test as well as stait unsteadiness and atactic gait were impressive. Biceps and brachioradial reflexes could not be attained. There also was a pallhypaesthesia of 3–4/8 at both ankles. Rest of neurological findings was correct, in particular, no paresis, pyramidal path signs, oculomotor or cerebellar signs were found. There was no history of pain. In a cranial MRI, subcortical changes in the white matter as well as laterally symmetrical lesions of the cerebral stem in the lemniscus medialis, along the spinothalamic fibers were observed (Fig. 1a). In an MRI of cervical and thoracic spine, a continuous circular intraspinal enrichment of contrast agent of the pia mater was visible. (Fig. 1b). For the differential diagnosis, an inflammatory DD metabolic genesis was considered. Results of motor evoked potentials indicated a left- and leg-emphasized lesion of central motor tracts to all four limbs. Cerebrospinal fluid (CSF) analysis showed a definite pleocytosis (131 leukocytes/ μ l). In cytological analysis of CSF activated lymphocytes and monocytes were apparent (Fig. 2). Moreover, CSF protein content (386 mg/ dl) was increased; a three-class reaction was found [IgG 77.3 mg/dl (44.9%), IgA 8.86 mg/dl (51.4%), IgM 3.87 mg/dl (74.3%) ]. Furthermore, CSF lactate was increased (4.6 mmol/l). Antibody titers for Borrelia burgdorferi were also clearly increased in CSF (IgG > 1700 U/ml, IgM 2.2 U/ml). Upon repeated questioning, the patient remembered a tick bite more than 12 months previously. Even in retrospect, she had not realized any discomfort (especially pain or cranial nerve dysfunction), except for progressive unsteadiness and gait disorder. In summary, the patient suffers from a neuroborreliosis stage III. Intravenous therapy with ceftriaxone 2 g was administered over 21 days. Discussion: The differential diagnosis for ataxia in adults is long and includes, among others, Multiple sclerosis, cerebellar ataxias, neuropathies, vitamin deficiencies, and to the rare Creuzfeldt-Jakob disease (Bassetti and Mumenthaler, 2012 ). Borreliosis is an infectious disease that passes through several stages and is caused by spirochetes of the species Borrelia. In addition to numerous other symptoms, the nervous system may also be involved. Here, a distinction is made between the acute and the chronic form. While the former primarily presents as meningoencephalitis, a typical manifestation of the chronic form is a spastic-atactic gait, accompanied by a bladder emptying disorder (Deutsche Gesellschaft für Neurologie (Hrsg), 2012 ). Chronic neuroborreliosis, with about 2%, is significantly less frequent than acute neuroborreliosis (98%) (Dersch and Rauer, 2016 ), and thus not the first aspect considered in a differential diagnosis of ataxia. The additionally existing symptoms (bladder emptying disorder, short-term memory disorders) and the conspicuous imaging prompted further evaluation.